ANALISIS KELAYAKAN APP-INVENTOR SEBAGAI BAHAN AJAR MATAKULIAH MOBILE PROGRAMMING MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Ida Mulyadi; Muhammad Faisal; Nurul Qalbi; Indra Aditya (P3M STMIK Profesional Makassar, 2023)
Media in the learning process is a tool or intermediary in the delivery of learning material that can provide more knowledge and experience to students. The advantage of App Inventor lies in the ease of programming, where users do not need to have basic programming knowledge, understand code, or have experience in IT, but the most important thing in making applications using App Inventor is how programmers use logic like when someone puts together a puzzle. . In this research, a feasibility study and analysis was carried out using the System Usability Scale (SUS) method so that it could improve the quality of learning and the novelty of teaching materials in the Makassar Professional STMIK environment. The sampling technique used in this research is random sampling or probability sampling. Based on the results of the recapitulation of the respondents' assessment, the average usability of the system was 72.83, then the grade of the assessment was determined. It was concluded that the results of the Recap of Usability Values showed that all attributes had a usability acceptance value by the user, the average value was above 68.00, namely 72.83. For Android users to be able to use APP-Inventor properly so that it is useful to support special learning activities in the Mobile Programming course.